2017
DOI: 10.1177/1010428317694298
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 promotes cell proliferation and cell adhesion–mediated drug resistance via the AKT pathway in multiple myeloma

Abstract: Eph receptor A4 (EphA4), a member of the erythropoietin-producing hepatocellular (Eph) family, has been reported to upregulate in several tumors. However, the role of EphA4 in multiple myeloma has not been clarified yet. In this study, we found that EphA4 promoted proliferation of multiple myeloma cells via the regulation of cell cycle. Besides, EphA4 was closely related to cell adhesion of multiple myeloma cells and promoted cell adhesion–mediated drug resistance by enhancing the phosphorylation levels of Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…Overexpression of EPHA4 is reported in various carcinomas such as gastric cancer (Miyazaki et al, 2013) and pancreatic cancer (Liu et al, 2014). EPHA4 is a transmembrane receptor tyrosine kinase, which interacts with cyclin-dependent kinase 5 and enhances the expression of p-AKT (Ding et al, 2017). We identified hyperphosphorylation of EPHA4 at Y602 (3.6fold) in our data.…”
Section: Alteration Of Protein Kinases and Phosphatases In Cigarette supporting
confidence: 59%
“…Overexpression of EPHA4 is reported in various carcinomas such as gastric cancer (Miyazaki et al, 2013) and pancreatic cancer (Liu et al, 2014). EPHA4 is a transmembrane receptor tyrosine kinase, which interacts with cyclin-dependent kinase 5 and enhances the expression of p-AKT (Ding et al, 2017). We identified hyperphosphorylation of EPHA4 at Y602 (3.6fold) in our data.…”
Section: Alteration Of Protein Kinases and Phosphatases In Cigarette supporting
confidence: 59%
“…The Eph receptor A4 ( EPHA4 ), a member of the erythropoietin‐producing hepatocellular (Eph) family, promotes cell adhesion of multiple myeloma cells by enhancing the phosphorylation levels of Akt probably due to its interaction with CDK5 . In our cellular system, the induction of EPHA4 in the hiPSC‐SLE line might influence the increase of pAkt levels .…”
Section: Discussionmentioning
confidence: 89%
“…Besides, it has been demonstrated that EPHA4 performs an important role in a lot of cellular processes, like promoting cell proliferation and cell adhesion-mediated drug resistance via the Akt signaling pathway [27]. While COL18A1 interacted with VTN and EPHA4, plays a crucial role in response of acute liver injury through binding α1β1 integrin on hepatocytes [28].…”
Section: Discussionmentioning
confidence: 99%